Analisis Pengaruh Gini Ratio Dan Jumlah Penduduk Terhadap Tingkat Kemiskinan Kabupaten/Kota Di Provinsi Aceh - Saleh, M.; Rizkina, Azka (Ekonomika Journal, 2021)
This research aims to analyze the influence of the Gini ratio and population on poverty districts/cities in Aceh. By using the ARDL panel model. The type of data used is data panel from 2010 to 2019 covering 23 districts/cities in Aceh. With total sample as many as 230 samples. The research results show that the Gini ratio and population have an influence against poverty in the short term. However, it has no effect in the long term.